Formulasi dan uji vikositas sediaan suspensi ekstrak labu air (lagenaria siceraria (molina) standly) dengan madu multiflora - Solikah Ana Estikomah Ana; Sri Wahyuni; Aisyah Muthmainnah (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2021)
Pumpkin water (Lagenaria siceraria (Molina) Standl) is a fruit that has a high water content that is efficacious as a cure for high fever due to thyphus or infection because it has cooling effect. This study aims to make suspensions of pumpkin extract and multiflora honey as a theraphy for fever thypoid. Suspended preparations are expected to provide a theraupetic effect which is faster and has good stability. Three suspension formulations ware made with sodium alginate suspending agent with a concentration of suspending agent 1%, 3%, 5%. Evaluation of suspensions preparations includes sedimentation organoleptic, viscosity. The best and most stable suspension preparation formula is suspension preparations with a 1% concentration of sodium alginate.